Histomorphological study of breast lesion in a tertiary care centre in Kathmandu - Khadka, Anu; Pudasaini, Sujata; Adhikari, Shreesti (Nepal Medical College Journal, 2023)
Various types of lesion from inflammation to carcinoma can affect the breast. Some lesions are common in young age group while others are more common in elderly age group. Accurate diagnosis is essential to relieve anxiety of patients. In case of carcinoma, early and accurate diagnosis can save the patient from metastases thus reducing mortality and morbidity. Histopathology plays a major role in distinguishing benign lesions from malignant lesions. Hospital based descriptive study was carried out in the Department of Pathology of a tertiary care centre in Kathmandu over a period of eleven months (1st September 2022 to 30th July 2023). A total of 52 cases of breast lesions were included in the study. Among 52 cases, 17 (33%) were non-neoplastic and 35 (67.0%) were neoplastic. Among neoplastic, 21 (40.3%) were benign and 14 (26.9%) were malignant. Among non neoplastic lesions, inflammatory lesion (17.3%) was the most common diagnosis. Among neoplastic lesion, fibroadenoma (34.6%) was the most common diagnosis. All cases of malignant breast lesions (26.9%) were diagnosed as invasive breast carcinoma, no special type. This study helped us to analyze the histopathological spectrum and prevalence of breast lesions in this part of our country. It is well known fact that the histomorphological study of the breast lesions is an important aspect for the diagnosis, management and prognosis of breast diseases.